Models of Self-Peptide Sampling by Developing T Cells Identify Candidate Mechanisms of Thymic Selection - Bains, Iren; van Santen, Hisse M.; Seddon, Benedict; Yates, Andrew J. (PLOS Computational Biology, 2013)
Author Summary T cells develop in the thymus, where they are vetted – they must respond weakly to self-antigens, but not so strongly as to risk causing autoimmunity. This selection process involves developing T cells being exposed to a large sample of self-peptides presented on specialised cells in the thymus, and deciding to die or to differentiate into mature T cells of either conventional or regulatory lineages. The rules by which T cells assimilate information from these interactions to make these decisions are not known. In this study we use previously published data to assess and discriminate between different models of thymic selection and find the most support for a model in which T cells vary their sensitivity to self-peptides during their development. This allows fate decisions to be made on the basis of as few as one peptide at a time, which allows for fine specificity in the selection process.